β-catenin regulates muscle glucose transport via actin remodelling and M-cadherin binding - Stewart W.C. Masson; Brie Sorrenson; Peter R. Shepherd; Troy L. Merry (Elsevier, 2020)
Objective: Skeletal muscle glucose disposal following a meal is mediated through insulin-stimulated movement of the GLUT4-containing vesicles to the cell surface. The highly conserved scaffold-protein β-catenin is an emerging regulator of vesicle trafficking in other tissues. Here, we investigated the involvement of β-catenin in skeletal muscle insulin-stimulated glucose transport. Methods: Glucose homeostasis and transport was investigated in inducible muscle specific β-catenin knockout (BCAT-mKO) mice. The effect of β-catenin deletion and mutation of β-catenin serine 552 on signal transduction, glucose uptake and protein-protein interactions were determined in L6-G4-myc cells, and β-catenin insulin-responsive binding partners were identified via immunoprecipitation coupled to label-free proteomics. Results: Skeletal muscle specific deletion of β-catenin impaired whole-body insulin sensitivity and insulin-stimulated glucose uptake into muscle independent of canonical Wnt signalling. In response to insulin, β-catenin was phosphorylated at serine 552 in an Akt-dependent manner, and in L6-G4-myc cells, mutation of β-cateninS552 impaired insulin-induced actin-polymerisation, resulting in attenuated insulin-induced glucose transport and GLUT4 translocation. β-catenin was found to interact with M-cadherin in an insulin-dependent β-cateninS552-phosphorylation dependent manner, and loss of M-cadherin in L6-G4-myc cells attenuated insulin-induced actin-polymerisation and glucose transport. Conclusions: Our data suggest that β-catenin is a novel mediator of glucose transport in skeletal muscle and may contribute to insulin-induced actin-cytoskeleton remodelling to support GLUT4 translocation.